20 ans d’Observatoire photographique des paysages dans le Parc naturel régional des Vosges du Nord - Romy Baghdadi (Projets de Paysage)
After nearly 20 years of almost uninterrupted extended photographic activity on the part of the Photographic Observatory of the Landscape, supplemented by mediation, pedagogical activities, and artistic and cultural promotion, the Vosges du Nord Regional Nature Park and the Alsace Champagne Ardenne Regional Environmental, Development and Housing Agency wanted to review the changes which occurred in the landscape during this period. They also wanted to reassess the process in the light of their regional development commitments, and namely commitment number 3 of being “a region which cares for its spaces and landscapes” (Parc 2014 Association). After having compiled a collection of more than 700 photographs taken from 200 different points of view, spanning a period of 20 years, and documenting changes in the landscape, the question was, what should the next step be ? The Photographic Observatory should not simply represent an impressive body of fine creative photographic works. It needs to pro-actively encourage discussion, provide answers and, above all, inspire initiatives. At this stage in its existence, its aim should be to render the constant changes as well as sudden transformations and successive territorial layers of the landscape visible and understandable but, above all, it should reveal the emergence of a new local landscape culture born of a collective perspective, while steering clear of any systematic consensual touristic imagery. Since its creation, the Photographic Observatory made it possible to promote the region through the theme of the landscape. This article starts by presenting some of the Observatory’s activities. Since January 2016 and, in anticipation of the 20th anniversary of the Observatory, the ambition is to confer a new dimension to the photographic archives. As a potential co-production partner in the development of projects, the Observatory should make better use of the shared maturity acquired through a retrospective view to contribute to the development of the region through its landscape. We shall see how the Vosges du Nord Regional Nature Park attempts to use these photographs to encourage the systematic use of images of the landscape in development projects. In summary, the question concerns how to privilege initially resorting to a vertical representation of a part of an area, the visible part, its perspective, successive interpretations and structural elements, rather than resorting to maps or plans, which are more often used but remain less palpable and less evocative for the inhabitants of the area.